Effect of sodium glucose cotransporter-2 inhibitors (SGLT-2is) on the clinical outcomes of patients with diabetic atrial fibrillation - Selim Aydemir; Sidar Şiyar Aydın; Emrah Aksakal; Onur Altınkaya; Murat Özmen; Oğuzhan Birdal (BMC Cardiovascular Disorders)
Abstract Background Diabetes mellitus (DM) and atrial Fibrillation (AF) are among the most common health issues. They are responsible for the highest rates of morbidity and mortality. The importance of sodium glucose cotransporter-2 inhibitors (SGLT-2is) in treating DM has increased significantly in recent years. In our article, we aimed to evaluate the effect of SGLT-2i on the clinical outcomes of AF patients with DM. Methods Our study is a retrospective, observational study. The patients with AF and DM were divided into two groups: those using SGLT-2i or not using SGLT-2i, and 3-year follow-up results were examined. The endpoints of the study were defined as all-cause death, the development of myocardial infarction (MI), major bleeding requiring hospitalization, and an ischemic cerebrovascular event (CVE). Differences between groups according to SGLT-2i use were analyzed. Results The study included 485 patients, 205 (42.3%) of whom were male and had an average age of 70.7 ± 9.7 years. A total of 138 of 485 patients (28.5%) received SGLT-2i. All-cause mortality was lower in the group receiving SGLT-2i (p < 0.001). Similarly, a significant reduction in major bleeding events was observed among those who received SGLT-2i treatment (p = 0.009). The incidence of CVEs was lower among SGLT-2i recipients, but the difference was not statistically significant (p = 0.066). SGLT2i usage did not mitigate the risk of MI development (p = 0.317). Conclusions In our study, SGLT-2i treatment was associated with a significant reduction in all-cause mortality and major bleeding in diabetic AF patients. Our study provides evidence of the clinical benefit of SGLT-2i in AF patients.